Decolonising the Nile River: Colonial Agreements as Impediments to Sustainable Basin-wide Cooperation - Mekonnen, Teferi (Ethiopian Journal of Social Sciences, 2021)
Attempts at resolving the two major problems in the history of the Nile waters issue, i.e. equitable Nile waters resource apportionment and the formation of a Basin-wide organisation to the benefit of all riparian states of the river, have largely failed. This paper argues that the disagreement over the utilisation of the Nile waters arises mainly from the 1929 and 1959 agreements that gave Egypt and the Sudan extensive rights over the river’s water. These agreements have been at the heart of the struggle over the Nile waters between Egypt and the Sudan, on one side, and the other upper riparian states, on the other. Egypt and the Sudan saw the agreements as historical legacies to be maintained, like colonial boundaries which African states inherited from colonialism, without modification in perpetuity. On the other hand, other upstream countries see Nile agreements as colonial relics and demand their right to a fair and equitable share of the Nile waters. This paper argues for decolonising the Nile River and fostering the cooperation of all riparian states in the spirit of Pan-Africanism. Therefore, urgent and concrete steps should be taken to revise all agreements of the colonial period and the 1959 Nile Waters Agreement, and to renegotiate a new Nile Waters Agreement to accommodate the interests of all riparian states. This agreement should be based on internationally accepted principles and commitment to a win-win solution.